Anesthetic Dilemmas for Dynamic Evaluation of the Pediatric Upper Airway. (December 2014) - Chatterjee, Debnath; Friedman, Norman; Shott, Sally; Mahmoud, Mohamed
Sleep cine magnetic resonance imaging and drug-induced sleep endoscopy are currently used to examine the patterns of dynamic airway collapse in children with obstructive sleep apnea. Providing anesthesia that mimics physiologic sleep in these children is a challenge but is critical for accurate interpretation of the airway evaluation. Anesthetic agents might negatively affect the upper airway evaluation. The anesthetic technique in these patients must be tailored to improve patient safety and obtain optimal study. This review focuses on the periprocedural challenges and anesthetic management of children presenting for dynamic evaluation of the upper airway.